Leveraging Technology to Promote Global Citizenship in Teacher Education in the United States and Brazil - Michael Kopish; Welisson Marques (Research in Social Sciences and Technology- OpenED Network, 2020)
With globalization and the increase of technology, collaborative work between institutions from different countries is a reality. Beginning in 2018, two teacher education programs, one in the United States and one in Brazil, developed a partnership to promote collaborative activities in curriculum and instruction, scholarship and research, and for student and faculty exchange. Critical pedagogy and social justice approaches to global citizenship education in teacher preparation guided the partnership’s collaborative activities toward the development of pre-service teachers’ global competencies and ability to integrate technologies as users and educators. This empirical research article presents an exploratory case study of a transnational, collaborative curricular project that leveraged technology in courses for pre-service teachers in the United States (n=12) and Brazil (n=10). The study explores the extent to which course content and activities facilitated pre-service teachers’ development of global competencies and ability to employ emerging technologies for learning and offers implications for practice.